PENGELOLAAN KEUANGAN BUMDES DESA TEKULAI HULU KECAMATAN TANAH MERAH - ASMARITA ASMARITA; ROSLIANA ROSLIANA; NOVRIANI SUSANTI; RIA FEBRINA (JURNAL AKUNTANSI DAN KEUANGAN, 2026)
Financial management of Village-Owned Enterprises (BUMDes) plays a crucial role in ensuring business sustainability and enhancing community welfare at the village level. Sound financial management is required to uphold the principles of transparency, accountability, effectiveness, and efficiency so that BUMDes can operate optimally. However, in practice, various challenges remain, including limited human resource capacity, simple financial recording systems, and the incomplete implementation of applicable accounting standards. This study aims to describe and analyze the financial management practices of BUMDes in Tekulai Hulu Village, Tanah Merah District. A qualitative descriptive approach was employed in this research. Data were collected through in-depth interviews, direct observation, and documentation involving BUMDes administrators and village government officials. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings indicate that financial management at BUMDes Tekulai Hulu has been implemented through the stages of planning, implementation, recording, and financial reporting. Nevertheless, these practices have not fully met the principles of transparency and accountability and are not yet fully aligned with prevailing accounting standards. The main obstacles identified include limited accounting knowledge among administrators, inadequate financial administration, and weak internal control mechanisms. This study is expected to serve as an evaluative reference and provide practical recommendations for BUMDes management and village governments in improving sustainable financial management practices.